GROWTH OF Grevillea robusta A. Cunn. IN THE CENTRAL DEPRESSION OF THE RIO GRANDE DO SUL, BRAZIL - Canto, Juliana Lorensi do (2004)
In this work the growth in diameter, merchantable volume and merchantable form factor as a function of the age of Grevillea robusta A. Cunn. were studied, in the area of Central Depression of Rio Grande do Sul, Brazil. For this purpose, dominant trees were sampled, cut down and cubic scaled according to the Smalian method. Next, slices of stem were taken for annual growth rings analysis. The measurements of the growth rings were accomplished through the technique of stem analysis, by measuring four radii. The results obtained for the estimate of growth indicated that several equations can be used for this purpose with high statistical precision. The medium growth, at 30 years of age, in diameter was 36.0 cm, merchantable volume, 1.2388 m3 and merchantable form factor, 0.79, indicating great potential for commercial reforestation.